Performance analysis of integrated collector system with immersed coil heat exchanger - Afolabi, L.O. (Trans Tech Publications Ltd, 2014)
The performance of integrated solar collector/thermal energy storage with immersed heat exchanger was investigated experimentally at the Solar Research Site, University Technology PETRONAS, (4.4224oN, 100.9904oE), Malaysia. The experimental set up consisted of 150 liters storage tank capacity with immersed coil heat exchanger, single glazing 1.5m2 flat plate collector with 15o tilt to the horizontal. The circulation of the working fluid was by forced in closed loop with a mini solar pump. Aluminum cell foam was attached to the absorber as extended surface. The surface of the collector was coated with black ornament to improve its absorption. The system was tested under clear skys, for two cases; with and without water drawn-off for seven days per case studied. The performance evaluation data obtained for case1 at the mean maximum solar intensity was 503.98 W/m2 were: maximum daily water temperature 63oC, average daily water temperature 46oC, collector efficiency 63 and system efficiency 43. Whilst for case 2, the mean maximum solar intensity was 473.11 W/m2, the maximum daily water temperature 54oC, average daily water temperature 39.36oC, collector efficiency 54 and system efficiency 39. The system efficiency for case 2 showed that the heat exchanger performed slighlty better and the water drawn-off effect is minimal. Â© (2014) Trans Tech Publications, Switzerland. All Rights Reserved.